Emergence of new phylogenetic lineage of Influenza D virus with broad antigenicity in California, United States - Huang, Chen (Emerg Microbes Infect, 2021)
Influenza D virus (IDV), with bovines as a primary host, circulates widely in cattle populations across North America and Eurasia. Here we report the identification of a novel IDV group with broad antigenicity in U.S. bovine herds, which is genetically different from previously known lineages of IDV.